Effect of irrigation levels and genotypes on barley (Hordeum vulgare L.) productivity and grain quality traits - Verma, R.K.; Kumar, A.; Thakral, S.K.; Ghasal, P.C. (Annals of Agricultural Research, 2019)
A field experiment was conducted during winter (rabi) season of 2011-2012 to study the effect of irrigation on growth, yield and malt quality of different genotypes of barley (Hordeum vulgare L.). The results revealed that grain and biological yield were higher under two irrigations than one irrigation. Malt quality characters such as bulk density, bold grains and protein content were higher while husk content, thin grains and malt recovery was lower under two irrigation than one irrigation. Among tested barley genotypes, number of spike were higher in BH 10-22 (110.8/m.r.l.), number of grains per spike in BH 10-06 (72.0), test weight in BH 09-44 (45.9 g), grain and biological yield in BH 902 (3.92 t ha-1 & 9.29 t ha-1, respectively), bold grains in BH 10-11 (86.11%), bulk density in BH 10- 35 (69.99 kghl–1), protein in BH 10-07 (9.63%) and malt recovery in BH 927 (85.78%) as compared to other genotypes. The interaction between irrigation and barley genotypes was also significant for most of the characters indicating differential behavior of barley genotypes to irrigation levels.